Therapeutic implication of autophagy in neurodegenerative diseases - Rahman, Md. Ataur; Rhim, Hyewhon (KOREAN SOCIETY BIOCHEMISTRY & MOLECULAR BIOLOGY, 2017)
Autophagy, a catabolic process necessary for the maintenance of intracellular homeostasis, has recently been the focus of numerous human diseases and conditions, such as aging, cancer, development, immunity, longevity, and neurodegeneration. However, the continued presence of autophagy is essential for cell survival and dysfunctional autophagy is thought to speed up the progression of neurodegeneration. The actual molecular mechanism behind the progression of dysfunctional autophagy is not yet fully understood. Emerging evidence suggests that basal autophagy is necessary for the removal of misfolded, aggregated proteins and damaged cellular organelles through lysosomal mediated degradation. Physiologically, neurodegenerative disorders are related to the accumulation of amyloid beta peptide and alpha-synuclein protein aggregation, as seen in patients with Alzheimer's disease and Parkinson's disease, respectively. Even though autophagy could impact several facets of human biology and disease, it generally functions as a clearance for toxic proteins in the brain, which contributes novel insight into the pathophysiological understanding of neurodegenerative disorders. In particular, several studies demonstrate that natural compounds or small molecule autophagy enhancer stimuli are essential in the clearance of amyloid beta and alpha-synuclein deposits. Therefore, this review briefly deliberates on the recent implications of autophagy in neurodegenerative disorder control, and emphasizes the opportunities and potential therapeutic application of applied autophagy.
Keywords: UNCONVENTIONAL SECRETORY PATHWAY; DEGRADING ENZYME-SECRETION; ALLEVIATES MEMORY DEFICITS; IN-VIVO MODELS; ALZHEIMERS-DISEASE; PARKINSONS-DISEASE; ALPHA-SYNUCLEIN; MOUSE MODEL; NERVOUS-SYSTEM; CAENORHABDITIS-ELEGANS